TOXIC EPIDERMAL NECROLYSIS DUE TO ACECLOFENAC - N.AJAY KUMAR; M.SHANTHI; NAVAJOTHI (International Journal of Pharma and Bio Sciences, 2013)
Toxic epidermal Necrolysis (TEN) are serious disorders commonly termed as idiosyncratic reactions to drug, the most common being antiepileptic(phenytoin, barbiturates, carbamazepine and lamotrigine), sulfonamides, trimethoprim, ampicillin, allopurinol and NSAIDS (especially phenylbutazone and oxicam derivatives). Here we report a case of TEN in a patient who developed the lesion after oral administration of ACECLOFENAC. These drugs have rarely been implicated in this disorder. The suspected drug in this case was aceclofenac. The patient was managed with antibiotics, corticosteroids and parenteral fluids and recovered well.